The Effect of Water Bath Temperature during Electrochemical Deposition of Zinc Oxide - Ainuddin, Ainun Rahmahwati; Ashraf Darus, Mohd Amirul; Ismail, Nurul Syahira; Kamdi, Zakiah; Yunos, Muhammad Zaini; Mohamed Hatta, Mohamed Nasrul; Hussin, Rosniza; Ibrahim, Siti Aida (Journal of Science and Technology, 2017)
Nanostructure Zinc Oxide (ZnO) is widely applied in various fields such as optoelectronics, sensors, transducers and biomedical sciences. Nowadays, there are many methods that can be used to produce ZnO thin film such as electrochemical deposition. This method is a process of converting or forming an oxide layer on the metal surface. The purpose of this research is to study the effect of water temperature on the morphology of ZnO during the electrochemical deposition process. ZnO nanostructures obtained after electrochemical deposition process is carried out at different water temperatures and a constant current density. Electrochemical deposition process was carried out when the water temperature reached 60, 65, 70, 75 and 80oC. During the deposition process, 0.05 M/L zinc nitrate is used as a single electrolyte. The analysis conducted is divided into four categories, namely FESEM, XRD, EDX and UV-Vis. As a result, the suitable water bath temperature for forming the ZnO morphology with an electric current density of 4 mA/cm2 is at 75oC and at this temperature it has a higher value of composition mass where is 0.61 % compare with other temperature. From the UV-Vis analysis, it shows the value of band gap is 2.87 eV when the temperature of water bath was 75oC. Various studies were conducted to produce ZnO nanotubes because it provide different forms of reaction temperature at constant current densities.